Penerapan Sosial Media Instagram Bisnis Dalam Upaya Memperluas Wilayah Pemasaran Pada UMKM D'party Karawang - Sulastri, Dini; Nurlenawati, Netti; Triadinda, Dexi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The development of the digital era has made social media one of the effective marketing media for MSMEs to expand marketing areas. This study aims to analyze the effectiveness of the application of Instagram business in improving the marketing of D'Party MSMEs in East Karawang. This research uses descriptive qualitative methods with data collection techniques through observation, documents and in-depth interviews with business owners, old consumers, new consumers, and social media experts. The results showed that the use of Instagram Business was able to increase market reach, interaction with customers, and the number of new customers by 25-30% when compared to the previous period. Instagram features such as stories, reels, and visual content-based marketing strategies proved effective in attracting customer attention and increasing engagement. In conclusion, the implementation of Instagram business is effective in the growth of D'Party MSMEs by expanding the market and increasing sales. The implication of this study is that future research is recommended to explore the influence of paid features such as Instagram ADS in increasing the effectiveness of digital marketing.